2022
DOI: 10.1177/15330338221075172
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of AI for Cancers Registered in A Mammography Screening Program: A Retrospective Analysis

Abstract: Purpose: To evaluate the performance of an artificial intelligence (AI) algorithm in a simulated screening setting and its effectiveness in detecting missed and interval cancers. Methods: Digital mammograms were collected from Bahcesehir Mammographic Screening Program which is the first organized, population-based, 10-year (2009-2019) screening program in Turkey. In total, 211 mammograms were extracted from the archive of the screening program in this retrospective study. One hundred ten of them were diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…The maturing AI software may also increase our ability to capture cancer. A diagnostic study for AI in a retrospective simulated screening setting found the highest cancer detection rate by teaming up radiologists and AI [ 23 ]. A recently published retrospective study by Kim et al also found AI to be able to detect mammographically occult cancers in dense breasts [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maturing AI software may also increase our ability to capture cancer. A diagnostic study for AI in a retrospective simulated screening setting found the highest cancer detection rate by teaming up radiologists and AI [ 23 ]. A recently published retrospective study by Kim et al also found AI to be able to detect mammographically occult cancers in dense breasts [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…AI framework using CNN has been employed for screening BC using DM. 34 AI enabled screening outperformed radiologist screening with an accuracy of 72.7%. Further combining AI and radiologist decision improved the detection performance of 83.6% accuracy with reduced false positive rates.…”
Section: Deep Learning-based Cad Approaches For Breast Cancer Diagnosismentioning
confidence: 99%
“…A study conducted in Korea using a similar AI program with 435 mammograms discovered that a cut-off value of 38.03 resulted in an AUC of 0.745 (95% CI, 0.701-0.785) with 69.1% sensitivity and 69.0% specificity in identifying suspicious microcalcifications [35]. Another study carried out in Turkey with 211 mammograms demonstrated that a cut-off value of 34.5 yielded an AUC of 0.853 (95% CI, 0.801-0.905) with 72.8% sensitivity and 88.3% specificity in identifying breast carcinoma [36].…”
Section: S a W I T R I D A R M I A T I E T A L Ai On Mammography Int...mentioning
confidence: 99%